Estimation of the tensile strength of UHPFRC layers based on non-destructive assessment of the fibre content and orientation - Mário Pimentel (2017)
In the present study we propose a procedure for estimating the tensile strength of thin ultra-high performance fibre-reinforced cement-based composite (UHPFRC) layers, which eliminates the need of extracting cores or samples from the structure. This procedure relies on a non-destructive testing (NDT) method based on the ferromagnetic properties of the steel fibres for estimating the parameters of the underlying physical model, namely, the fibre content and the fibre orientation factor, and on laboratory tensile tests for estimating the equivalent rigid-plastic fibre-to-matrix bond strength. An experimental program was developed for establishing the relation between the NUT measurements and the orientation parameters determined from image analysis. Following the proposed procedure, the tensile strength of 36 specimens with varying fibre content and fibre orientation distributions is estimated based on the magnetic measurements and compared to experimental results. The good correlation that is found demonstrates the significance of the proposed NDT method in the implementation of quality control procedures of thin UHPFRC elements/layers.